2020
DOI: 10.1101/2020.07.31.20165829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation Considered Epidemiological Model for the Prediction of COVID-19 Trend in Tokyo, Japan

Abstract: Background: Coronavirus Disease 2019 (COVID19) currently poses a global public health threat. Although no exception, Tokyo, Japan was affected at first by only a small epidemic. Medical collapse nevertheless nearly happened because no predictive method existed for counting patients. A standard SIR epidemiological model and its derivatives predict susceptible, infectious, and removed (recovered/deaths) cases but ignore isolation of confirmed cases. Predicting COVID19 trends with hospitalized and infectious peop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thus, Shayak and coathours numerically investigated the simplest retarded logistic equation with time delay to model the spread of COVID-19 in a city and demonstrated that solution of the model is significantly sensitive to small changes in the parameter values (Shayak et al, 2020). In the same time, more conventional SEIR-based delay differential equation models were proposed to reproduce the COVID-19 dynamics in Germany, China, South Korea, India and Japan (Götz and Heidrich, 2020; Menendez, 2020; Sharma et al, 2021; Utamura et al, 2020) and to predict the epidemic dynamics in Italy and Spain when it was in its early stages. However, these models did not take into account asymptomatic carriers and non-testing subpopulations as well as the progression of the disease’s severity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Shayak and coathours numerically investigated the simplest retarded logistic equation with time delay to model the spread of COVID-19 in a city and demonstrated that solution of the model is significantly sensitive to small changes in the parameter values (Shayak et al, 2020). In the same time, more conventional SEIR-based delay differential equation models were proposed to reproduce the COVID-19 dynamics in Germany, China, South Korea, India and Japan (Götz and Heidrich, 2020; Menendez, 2020; Sharma et al, 2021; Utamura et al, 2020) and to predict the epidemic dynamics in Italy and Spain when it was in its early stages. However, these models did not take into account asymptomatic carriers and non-testing subpopulations as well as the progression of the disease’s severity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their model, the patient that has passed an assumed period is quarantined once with an assumed probability, but if not quarantined, a chance of being quarantined is not left any longer. On the other hand, Utamura et al [17] developed a model named as "Apparent Time Lag Model (ATLM)" in that all the infectious patients are quarantined after passing an assumed period (14 days). Here, I have developed a new model introducing a compartment for quarantine possible infectious patients, where patients have a chance to be quarantined with a quarantine rate.…”
Section: Introductionmentioning
confidence: 99%
“…In their model, the patient that has passed an assumed period is quarantined with an assumed probability, but if not quarantined, a chance of being quarantined is not left any longer. On the other hand, Utamura et al [17] developed a model in that all the infectious patients are quarantined after passing an assumed period (14 days).…”
Section: Introductionmentioning
confidence: 99%